Successful management of serious disopyramide poisoning. Issue 654 (April 1980) - Holt, D. W.; Helliwell, M.; O'Keeffe, B.; Hayler, A. M.; Marshall, C. B.; Cook, G.
Abstract : A case of deliberate disopyramide overdosage is described. Circulatory collapse was treated by means of a large dose of isoprenaline, and charcoal haemoperfusion was used in an attempt to enhance the elimination of disopyramide. The suitability of this treatment regime is discussed in the light of findings from animal studies and the implications for the management of the disopyramide-poisoned patient are considered.